A Commentary on the REA 2018 Annual Meeting. Issue 3 (27th May 2019) - Kim-Cragg, HyeRan
Abstract: This commentary offers a "thick description" and analysis of the 2018 Religious Education Association (REA) meeting from my perspective as a racialized woman from Canada, a member of the REA board, and a professor who teaches anti-racism, preaching, and postcolonial theories among other subjects. My commentary seeks to leave a trail, making a permanent and public record. We, as religious educators, are responsible to pass down teachings to the next generation. Many wise elders have taught that history returns but it never repeats in the same way. We must not forget but remember what happened so that when it returns we will be ready.